Brazilian Legal Amazon and the Theory of Agrarian Conflicts - Ferreira, Gustavo Henrique Cepolini (Revista Cerrados, 2023)
The analysis of agrarian conflicts in the Brazilian Legal Amazon involves a theoretical and methodological endeavor to comprehend the essence of these conflicts in terms of class struggle and the ongoing territorial disputes in the Amazon region, and by extension, throughout Brazil. In this context, this paper employs the framework of Agrarian Geography in conjunction with data from the Pastoral Land Commission (CPT) to map conflicts and murders in Brazilian rural areas and the Amazon during two time frames, i.e., from 1964 to 1945 and from 1985 to 2020. By doing so, this papers highlights the recurrence of barbarism in Amazon rural areas and its implication for Brazilian society.